INFLUENCE OF BIOPHILOSOPHICAL KNOWLEDGE ON PERSONALITY DEVELOPMENT AND HUMANISTIC WORLD VIEW FORMATION OF FUTURE PHYSICAL EDUCATION TEACHERS IN THE UNIVERSITIES OF UKRAINE - Kostiuchkov, Serhii; Korshun Tatіana; Shvets, Tatiana; Koval, Viktoriia; Voloshyn, Oleksandr (Revista Inclusiones, 2020)
The goal of the research is to determine the degree of correlation between the teaching of biophilosophy in the complex of socio-humanistic disciplines and the formation of future Physical Education teachers’ humanistic world view in the universities of Ukraine. Materials: the method of scientific sources analysis, the method of focus group research, and mathematical statistics have been applied. The proposed syllabus of the discipline “Fundamentals of Biophilosophy” for the faculties of Physical Education and Sport is based on the biophilosophical concept of education developed by one of the authors and settled in the higher education system of modern Ukraine. The results of the research offer the possibility to make adjustments to the scope and content of the complex of socio-humanistic disciplines taught to future Physical Education teachers in the universities of modern Ukraine.